Diagnostics and prognostics with acoustic emission, vibration and spectrometric oil analysis for spur gears; a comparative study - Tan, Chee Keong; Irving, Phil E.; Mba, David (Learned and Professional Society Publishers, 2005)
Whilst vibration and spectrometric oil analysis for gear fault diagnosis are well established, the application of AE to this field is still in its infancy. This paper describes an experimental investigation on spur gears in which natural pitting was allowed to occur. Throughout the test period, AE, vibration and spectrometric oil samples were monitored continuously in order to correlate and compare these techniques to natural life degradation of the gears. It was observed that the AE technique was the most sensitive in detecting and monitoring pitting.
Keywords: Acoustic Emission